Mediating Public Aspirations: Institutional Filtering, Political Representation, and the Practice of Legislative Recess in Subnational Governance - Talitha Purnama Adristari; Juwita Pratiwi Lukman (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
This article examines legislative recess as a sociological mechanism that mediates public aspirations within subnational governance, challenging normative assumptions of direct political representation. While public participation is often conceptualized as a linear conduit between citizens and policymaking, this study argues that such participation is structured by institutional procedures, power relations, and administrative constraints. Focusing on legislative recess practices, the research analyzes how public aspirations are articulated, negotiated, and selectively translated into policy-relevant claims. Using a qualitative descriptive-analytical approach, the study draws on participant observation of recess activities, in-depth interviews with legislators, secretariat staff, and community representatives, and analysis of official documents, including recess reports, legislative proposals, and budgetary regulations. Thematic analysis is employed to capture the institutional dynamics shaping aspiration processing. The findings demonstrate that legislative recess operates as an arena of mediated representation rather than a direct representational channel. Public aspirations are subjected to layered institutional filtering based on jurisdictional authority, budgetary feasibility, and thematic prioritization, resulting in structural selectivity. Aspirations aligned with institutional logics are more likely to be accommodated, while others are systematically marginalized without formal exclusion. The study contributes to sociological theory by reframing legislative recess as a process of institutional mediation and introduces the concepts of mediated public aspirations and institutional filtering to explain representational inequality within democratic governance, particularly in subnational contexts of the Global South.